Reducing discards without reducing profit: free gear choice in a Danish result-based management trial. (8th January 2017) - Mortensen, Lars O.; Ulrich, Clara; Eliasen, Søren; Olesen, Hans Jakob
Abstract : The 2013 Common Fisheries Policy introduced a landing obligation on a range of species, bringing more focus on the full accountability of all catches. To investigate the potentials and challenges of these paradigm shifts, a 6-months 'unrestricted gear' trial was performed in Denmark in 2015. Twelve trawlers were challenged to test their own solutions to reduce unwanted bycatch and/or choke species, while maintaining profitable. The participating fishers tested different options depending on their fishery and the type of issues they faced individually, and adjusted their test fishery over time through incremental small steps. Nine vessels reduced discard ratio in the test fishery, one showed no difference between test and control fishery, while two vessels displayed an increase in discard ratio. Catch compositions also differed, with fewer "choke species" occurring in the test fisheries and a more valuable size composition. Ultimately, despite smaller landings in multiple vessels, no vessel showed reduction in value-per-unit-effort (VPUE) and one Baltic vessel significantly increased the VPUE. This trial showed that relaxing technical regulations combined with proper incentives has a potential to provide some flexibility to cope with the landing obligation, where unwanted catches could be reduced to some extent without negative effects on economic viability.